Demographic Parameters and Growth Projection of Spangled Ebony Langur Population (Trachypithecus auratus) in the Kerandangan Natural Tourism Park Protection Block Through a System Dynamics Approach - Putri, Regina Natasya; Syaputra, Maiser; Anwar, Hairil (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Indonesia is a country with rich biodiversity of flora and fauna, one of which is the langur from the primate family. Langurs are also listed on the 2008 International Union for Conservation of Nature and Natural Resources (IUCN) Red List as a primate species classified as vulnerable due to population decline and habitat degradation. Spangled Ebony Langurs play a crucial ecological role, influencing forest regeneration patterns and tree species diversity in their habitat. The purpose of this study was to provide information on demographic parameters and population growth of Spangled Ebony Langurs (Trachypithecus auratus) in Kerandangan Nature Tourism Park. The research method was carried out using the Line Transect method. The results of the study found 2 groups of Spangled Ebony Langurs with a total of 57 individuals. Distribution of structural patterns. Group size ranged from 27 to 30 individuals, with an overall population density of 0.35 individuals per hectare, a sex ratio of 1:8, and a birth rate of 0.26. The total population increased from 57 individuals (Year 1) to 68 individuals (Year 5), with a consistent population increase every year. This simulation assumes a constant birth rate of 26% per year and a death rate of 10% per year. In the fifth year, the population reached 68 individuals, with 2 births and 0 deaths. In conclusion, the langur population is predicted to increase steadily over the next 5 years. In the fifth year, the population is estimated to reach 68 individuals.